Variability of the main elements of sweet sorghum productivity - A. E. Romanyukin; N. A. Kovtunova; V. A. Shurshalin; G. M. Ermolina (Зерновое хозяйство России, 2022)
Sorghum is one of the most adaptable and undemanding forage crops cultivated in arid zones. The crop is characterized with high quality foliage, which can be used in fodder production in various forms (both in single-crop silage and in multi-crop mixtures). The purpose of the current study was to estimate the variability of the main productivity elements of sweet sorghum green mass depending on weather indicators. The initial material was presented by 180 collection samples of sweet sorghum from Russia, the USA and Ukraine. There have been used conventional breeding methods, such as hybridization, selection and inbreeding. The weather conditions during the study years of 2017–2021 were contrasting. The hydrothermal coefficient for the vegetation period of sorghum indicates that the year of 2018 was the driest one (HThC = 0.38). The variability coefficient of collection samples of sweet sorghum according to green mass productivity has shown a strong variability of this indicator (V = 27–35%). The green mass productivity had a close direct correlation with the length of a leaf (0.73±0.05) and an average correlation with its width (0.61±0.06). The variability coefficient has shown that the samples of sorghum collection had an average variability according to the traits ‘leaf length’ (V = 15.3%) and ‘leaf width’ (V = 11.8%), and were stable according to the trait ‘number of leaves per plant’ (V = 7.4%). Correlation and regression analysis has shown that ‘leaf length’ had an average inverse correlation with air temperature (r = –0.42±0.06) and a strong direct correlation with precipitation (r = 0.78±0.05). The trait ‘leaf width’ is practically independent of weather conditions. The number of leaves had an average negative correlation with air temperature (r = –0.55±0.06), and a weak correlation with amount of precipitation. A leaf length and width are marker indicators of high productivity, so they can be used in plant selection for productivity.